2015
DOI: 10.1111/jai.12741
|View full text |Cite
|
Sign up to set email alerts
|

Post-thaw storage of sperm from various salmonid species

Abstract: Summary The effects of post‐thaw storage on the motility and fertilizing capacity of cryopreserved sperm were investigated in four salmonid species, including the Adriatic grayling (Thymallus thymallus; five males), rainbow trout (Oncorhynchus mykiss; six males), marble trout (Salmo marmoratus; five males) and the brown trout (Salmo trutta m. Fario; six males). The sperm of rainbow trout and marble trout was cryopreserved in the presence of either methanol or dimethyl‐sulfoxide (DMSO) as a cryoprotectant; for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…Our recent study on the Persian sturgeon, Acipenser persicus (Aramli and Nazari ) and also studies performed on the Adriatic grayling, rainbow trout, marble trout and brown trout (Horvath et al. ) demonstrated that the motility and fertilizing ability of cryopreserved sperm of these salmonid species can be preserved up to 60 min of post ‐ thaw storage of semen. In another study, Dreanno et al.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our recent study on the Persian sturgeon, Acipenser persicus (Aramli and Nazari ) and also studies performed on the Adriatic grayling, rainbow trout, marble trout and brown trout (Horvath et al. ) demonstrated that the motility and fertilizing ability of cryopreserved sperm of these salmonid species can be preserved up to 60 min of post ‐ thaw storage of semen. In another study, Dreanno et al.…”
Section: Discussionmentioning
confidence: 89%
“…However, these parameters significantly decreased after 60 min of post-thaw storage. Our recent study on the Persian sturgeon, Acipenser persicus (Aramli and Nazari 2014) and also studies performed on the Adriatic grayling, rainbow trout, marble trout and brown trout (Horvath et al 2013) demonstrated that the motility and fertilizing ability of cryopreserved sperm of these salmonid species can be preserved up to 60 min of postthaw storage of semen. In another study, Dreanno et al (1997) reported that after cryopreservation of turbot sperm, the percentage of motile frozen-thawed spermatozoa was significantly lower than that of fresh sperm, whereas the velocity and duration of motion were not significantly modified.…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first report concerning the examination of the effect of the storage period on the postthaw sperm motility parameters of brook trout. Preliminary studies performed on the Adriatic grayling, rainbow trout, marble trout, and brown trout [12] demonstrated that the fertilizing ability of cryopreserved sperm of these salmonid species can be preserved up to 60 minutes of postthaw storage of semen. Prolonged handling time of brook trout thawed semen could lead to better organization of hatchery work because the thawing procedure of several sperm samples for fertilization trials is time consuming.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of storage following thawing was also presented in various fish species (salmonids, sturgeon, perch etc.) (Aramli & Nazari, 2014;Bernáth et al, 2015;Horváth et al, 2015). The methods described above can support selective breeding and conservation programmes, as well as the hatchery practice in various fish (Aramli, Nazari, & Gharibi, 2015;Cabrita et al, 2010;Glenn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%